2004
DOI: 10.1029/2003jd004117
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal cycle of convection, clouds, and water vapor in the tropical upper troposphere: Satellites versus a general circulation model

Abstract: [1] Global high-resolution (3-hourly, 0.1°Â 0.1°longitude-latitude) water vapor (6.7 mm) and window (11 mm) radiances from multiple geostationary satellites are used to document the diurnal cycle of upper tropospheric relative humidity (UTH) and its relationship to deep convection and high clouds in the whole tropics and to evaluate the ability of the new Geophysical Fluid Dynamics Laboratory (GFDL) global atmosphere and land model (AM2/LM2) to simulate these diurnal variations. Similar to the diurnal cycle of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
233
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(271 citation statements)
references
References 47 publications
(162 reference statements)
37
233
1
Order By: Relevance
“…Diurnal variability in the Earth system that defines such signatures has been studied extensively (e.g., Nitta and Sekine, 1994;Webster at al., 1996;Soden, 2000;Yang and Slingo, 2001;Wood et al, 2002;Nesbitt and Zipser, 45 2003;Taylor, 2012). However, discrepancies persist when comparing the diurnal cycles in observations and models (e.g., Betts and Jakob, 2002;Dai and Trenberth, 2004;Slingo et al, 2004;Tian et al, 2004;Itterly and Taylor, 2014). These discrepancies highlight a lack of understanding, yet it is essential we can correctly represent diurnal variability since it constitutes a fundamental forcing cycle for our weather and climate.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Diurnal variability in the Earth system that defines such signatures has been studied extensively (e.g., Nitta and Sekine, 1994;Webster at al., 1996;Soden, 2000;Yang and Slingo, 2001;Wood et al, 2002;Nesbitt and Zipser, 45 2003;Taylor, 2012). However, discrepancies persist when comparing the diurnal cycles in observations and models (e.g., Betts and Jakob, 2002;Dai and Trenberth, 2004;Slingo et al, 2004;Tian et al, 2004;Itterly and Taylor, 2014). These discrepancies highlight a lack of understanding, yet it is essential we can correctly represent diurnal variability since it constitutes a fundamental forcing cycle for our weather and climate.…”
Section: Introductionmentioning
confidence: 96%
“…CC BY 4.0 License. and window (11 μm) channel radiances from multiple geostationary satellites spanning global longitude, Tian et al (2004) showed that deep convection in the tropics acts to moisten the upper troposphere via the evaporation of anvil clouds generated by deep convection. This increase in UTH can be prevalent over large spatial extents and will delay the increase in OLR after the convective cloud has dissipated due to continued absorption of the more intense radiation originating from warmer, lower 385 altitudes.…”
Section: Rows 2-4) a Lag 370mentioning
confidence: 99%
See 1 more Smart Citation
“…The diurnal cycle in UTH is reported to have an amplitude of 2-6% (Soden, 2000;Tian et al, 2004), with different peak-times for regions above ocean or land. However, as the amplitude of the diurnal cycle is relatively low compared to the accuracy of the individual measurements, this effect is also considered to be of minor importance here.…”
Section: Considerations For Creating Climatologiesmentioning
confidence: 99%
“…Global Circulation Models (GCMs) simulations are sensitive to cloud microphysics when we calculate heating profiles due to clouds [Clement and Soden, 2005]. These clouds comprise a significant portion of stratiform precipitation [Cheng and Houze, 1979] and water vapor transport from the lower atmosphere to upper atmosphere [Tian et al, 2004], which are also closely associated with properties of cloud particles inside anvils (e.g., microphysical composition, organization, etc.). Tropical anvil clouds have been widely studied from the radiative and hydrological perspectives during the last two decades with satellite observations and high-resolution GCM simulations [e.g., Houze, 1982;Johnson and Young, 1983;Yuan et al, 2011], but cloud dynamics, a more difficult problem, has received relatively less attention.…”
Section: Introductionmentioning
confidence: 99%